2018
DOI: 10.1080/02656736.2018.1484183
|View full text |Cite
|
Sign up to set email alerts
|

Multiple antenna placement in microwave ablation assisted by a three-dimensional fusion image navigation system for hepatocellular carcinoma

Abstract: 2018) Multiple antenna placement in microwave ablation assisted by a three-dimensional fusion image navigation system ABSTRACT Purpose: This study was conducted to compare a three-dimensional (3D) fusion image navigation system (FINS) with ultrasound (US) for guiding percutaneous microwave ablation (PMWA) for treatment of hepatocellular carcinoma (HCC). Materials and methods: This is a retrospective, non-randomized, comparative study. Our team developed a 3D FINS and used it to guide PMWAs for HCCs in 19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…This strategy had comparable accuracy with CT or MRI scan at 24 h after ablation and can greatly reduce the re-treatments [34]. Another solution is to employ fusion imaging systems in guidance of thermal ablation, these techniques can provide better contrast resolution and improve intra-procedural evaluation of ablation margin [30,31,35]. Insertion of the antenna into the center of tumor is commonly used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy had comparable accuracy with CT or MRI scan at 24 h after ablation and can greatly reduce the re-treatments [34]. Another solution is to employ fusion imaging systems in guidance of thermal ablation, these techniques can provide better contrast resolution and improve intra-procedural evaluation of ablation margin [30,31,35]. Insertion of the antenna into the center of tumor is commonly used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we performed multiple overlapping ablations by switching the insertion point, it can produce larger and more homogeneous ablation zone. Recently, multi-applicator ablation devices have been proved safe and effective in facilitating MWA [35]. It can result in simultaneous heat input into the target area and at the same time, shorten the total ablation time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to treatment e cacy, Zhang et al (42) showed a higher complete ablation rate in the rst session (3 days after ablation) when using stereotactic EM guidance, but equal primary technique e cacy at 1 month. Schaible et al (31) reported a signi cantly higher primary technique e cacy when using robotic targeting in a retrospective comparative study.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Incorporating 3D visualizations can lead to complete ablations and higher clinical success rates on the first ablation attempt, as well as fewer sessions overall relative to 2D US when subsequent attempts are required. 16,18 Computed tomography images can provide 3D multiplanar images to visualize the needle-like applicators, but repeated CT scans are performed at the cost of increased procedure time and radiation dose to the patient. MR imaging has been used as it offers advantages such as improved soft-tissue contrast and the potential for real-time treatment monitoring, but can again increase procedure time and is not readily accessible in many countries due to the sophisticated technology required.…”
Section: Introductionmentioning
confidence: 99%